2015
DOI: 10.1002/ajmg.a.37282
|View full text |Cite
|
Sign up to set email alerts
|

Dysspondyloenchondromatosis (DSC) associated with COL2A1 mutation: Clinical and radiological overlap with spondyloepimetaphyseal dysplasia‐Strudwick type (SEMD‐S)

Abstract: Dysspondyloenchondromatosis (DSC) is a rare skeletal dysplasia characterized by enchondroma-like lesions and anisospondyly. The former leads to discrepancies in limb length, and the latter, to progressive kyphoscoliosis. Two recent cases have highlighted the genetic heterogeneity of DSC, one demonstrating the presence and, the other, the absence of a COL2A1 mutation. This may have important clinical implications, for example, screening for complications including atlanto-axial instability associated with type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…In a study of COL2A1-related dysplasias, Terhal et al [2012] showed that a glycine substitution in the triple helical domain is the most common type of pathogenic mutation in the COL2A1 gene. Missense mutations resulting in substitution of the glycine residue within triple helical domain of COL2A1 with a bulkier amino acid, such as arginine or aspartic acid, are known to be pathogenic [Merrick et al, 2015]. The reported 2 heterozygous missense mutations, c.2258 G>A (p.Gly753Asp) and c.1799 G>A (p.Gly600Asp), by Nakane et al [2011] and Merrick et al [2015] lie within the triple helical domain and cause the substitution of glycine to aspartic acid, as found in our patient 2.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…In a study of COL2A1-related dysplasias, Terhal et al [2012] showed that a glycine substitution in the triple helical domain is the most common type of pathogenic mutation in the COL2A1 gene. Missense mutations resulting in substitution of the glycine residue within triple helical domain of COL2A1 with a bulkier amino acid, such as arginine or aspartic acid, are known to be pathogenic [Merrick et al, 2015]. The reported 2 heterozygous missense mutations, c.2258 G>A (p.Gly753Asp) and c.1799 G>A (p.Gly600Asp), by Nakane et al [2011] and Merrick et al [2015] lie within the triple helical domain and cause the substitution of glycine to aspartic acid, as found in our patient 2.…”
Section: Discussionmentioning
confidence: 74%
“…Missense mutations resulting in substitution of the glycine residue within triple helical domain of COL2A1 with a bulkier amino acid, such as arginine or aspartic acid, are known to be pathogenic [Merrick et al, 2015]. The reported 2 heterozygous missense mutations, c.2258 G>A (p.Gly753Asp) and c.1799 G>A (p.Gly600Asp), by Nakane et al [2011] and Merrick et al [2015] lie within the triple helical domain and cause the substitution of glycine to aspartic acid, as found in our patient 2. Glycine to glutamine substitution, as found in our patient 1, has not been reported in DSC patients before.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations